(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research aims to identify the extent of commitment of internal auditors in the Syrian private banks to the ethical standards of the auditing profession, which are represented: independence, integrity, transparency, confidentiality, credibility, and professional competence. The research relied on the descriptive analytical approach, where a questionnaire containing questions related to the aspects of the research was prepared and developed, and it was distributed to a sample of (14) internal auditors working in the internal audit departments in private banks in Syria, and the number targeted (11) (Bank, while Islamic banks were excluded, as they are subject to the Sharia audit department (according to the provisions of Islamic Sharia), and accordingly, (48) questionnaires were distributed to all the auditors in the internal audit departments in private banks, and (41) questionnaire with a response rate (41) were retrieved. 85.42%). The research found that the degree of commitment of the internal auditors in the banks under study to the ethical standards of the auditing profession: independence, integrity, transparency, confidentiality, reliability, and professional competence, was significant.